Periradicular Surgery of Human Permanent Teeth with Calcium-Enriched Mixture Cement - Asgary, Saeed; Ehsani, Sara (Iranian Endodontic Journal, 2013)
Introduction: Root-end preparation and restoration with an endodontic material are required when nonsurgical endodontic retreatment has failed or is impossible. The present clinical study reports the treatment outcomes of periradicular surgery using calcium-enriched mixture (CEM) cement. Materials and Methods: A prospective outcome study of periradicular surgery using CEM was conducted on 14 permanent teeth with persistent apical periodontitis. Using a standardized surgical protocol, 2-3 mm of the root apex was resected; approximately 3 mm deep root-end cavities were ultrasonically prepared and filled with CEM cement. All patients were available for recall. Results: Clinical and radiographic examination revealed complete healing of periradicular lesions, i.e. regeneration of periodontal ligament and lamina dura in 13 teeth (93% success) during a mean time of 18 months; moreover, the teeth were functional and asymptomatic. Conclusion: Favorable treatment outcomes in this prospective clinical study suggested that CEM cement may be a suitable root-end filling biomaterial.